2010
DOI: 10.1542/peds.2010-2575
|View full text |Cite
|
Sign up to set email alerts
|

Management of Food Allergy in the School Setting

Abstract: Food allergy is estimated to affect approximately 1 in 25 school-aged children and is the most common trigger of anaphylaxis in this age group. School food-allergy management requires strategies to reduce the risk of ingestion of the allergen as well as procedures to recognize and treat allergic reactions and anaphylaxis. The role of the pediatrician or pediatric health care provider may include diagnosing and documenting a potentially life-threatening food allergy, prescribing self-injectable epinephrine, hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 36 publications
(36 reference statements)
1
92
0
3
Order By: Relevance
“…Previous studies determined that only 25% to 28% of students who have asthma have a written plan on file with their school. 19,20 In addition, although food allergy management plans are widely recommended as a best practice for schools, 8,[21][22][23] their use in US school districts has been inconsistent. For example, a Mississippi study found that statewide variation in the use of school health management plans ranged from 0% to 37% among food allergic students.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies determined that only 25% to 28% of students who have asthma have a written plan on file with their school. 19,20 In addition, although food allergy management plans are widely recommended as a best practice for schools, 8,[21][22][23] their use in US school districts has been inconsistent. For example, a Mississippi study found that statewide variation in the use of school health management plans ranged from 0% to 37% among food allergic students.…”
Section: Discussionmentioning
confidence: 99%
“…42 Conseguir que la actividad de los niños en todos los ámbitos sea segura es un verdadero desafío, por lo que se requieren estrategias de prevención y de manejo terapéutico ante la presentación de síntomas, en especial la anafilaxia. 40 Las reacciones alérgicas por alimentos pueden ocurrir en el aula, zona de juegos, cantina, transporte escolar y excursiones. Los síntomas iniciales suelen ser leves y difíciles de reconocer por lo siguiente: a. Falta de diagnóstico previo.…”
Section: 33unclassified
“…10,11 Se deberían rotular los productos y alimentos aptos para su uso, cuidar la limpieza de las superficies y utensilios e impedir que los niños con riesgo compartieran alimentos. 40,43 La familia o responsables del niño deberán realizar lo siguiente: a. Informar a la escuela sobre la alergia de su hijo. b. Aportar un informe médico actualizado con las pautas de rutina y para la urgencia.…”
Section: 40unclassified
“…19 Pediatricians should partner with local health departments and school districts and child welfare agencies to be aware of programs for children and families that address certain needs, such as injury prevention, child maltreatment prevention, lead poisoning, environmental tobacco smoke control, breastfeeding promotion, overweight/obesity prevention, asthma, perinatal care, trauma, child abuse prevention, and disaster preparedness. [20][21][22][23] One example of a pediatric/public health approach would be to ensure that children's issues are addressed in disaster planning/response.…”
Section: Partnering With Public Healthmentioning
confidence: 99%
“…Pediatricians should work together with public health departments, school districts, [21][22][23] child welfare agencies, community and children' s hospitals, and colleagues in related professions to identify and decrease barriers to the health and well-being of children in the communities they serve. 26,27 In addition, pediatricians should have access to information about community programs and resources that could affect the health and well-being of the children in their community.…”
Section: Recommendationsmentioning
confidence: 99%